Problematika Opsi Pembayaran Kembali Pinjaman Extended Fund Facilities-IMF: Suatu Analisis Ekono-Politik tentang Sebab Akibat dan Skenario Solusinya - Prapti, Endang Sih (Unisia, 2016)
The author of article below declares that the main problem in Indonesia economy is not only exit strategy of IMF, but also because of EFF-IMF will end on December 31, 2003., and MPR decided to stop it based on Tap MPR No.VI year 2002. In this respect; it needs to think way how to repay debt from EFF-IMF. The following criteria that Indonesia still needs the trust of international market, Indonesia should grow self confident, and Indonesia can be an expectation in national and integrity of Indonesia. According to writer that Indonesia should consider to choose option cash payment be tween 5,4-8,4 billion US. Dollars to propose toward reforming IMF.